Quantifying Foreign Direct Investment Productivity Spillovers in China: A Computable General Equilibrium Model1. Issue 4 (December 2013) - Deng, Ziliang; Falvey, Rod; Blake, Adam
<x xml:space="preserve">Abstract</x> For the purposes of this study, we will construct a static monopolistically‐competitive computable general equilibrium model to quantify the endogenous productivity spillovers from foreign and domestic firms, using the Chinese economy as a case study. Our simulation results indicate: (i) that the net spillover effects are positive in terms of national total output, GDP and welfare; (ii) that both state‐owned and privately‐owned firms benefit, but that private firms benefit more; (iii) that industries with large volumes of foreign direct investment (FDI) do not necessarily observe the largest spillover effects; and (iv) that the spillover effects become more prominent when the initial market structure is more concentrated.